Sub-Chronic Toxicity Test of Solid Self Nanoemulsifying Drug Delivery System (S-Snedds) Hydrochlorothiazide in Male Rats - Asep Nurrahman Yulianto; Wahyu Widyaningsih; Iis Wahyuningsih; Ilham Fadilah; Tatang Tajudin (Indonesian Journal of Pharmacy and Natural Product, 2025)
Hydrochlorothiazide (HCT) is a diuretic thiazide that is commonly used in the treatment of hypertension, although it exhibits has low bioavailability. The development of the Solid Self-Nanoemulsifying Drug Delivery System (S-SNEDDS) is expected to be able to increase the solubility and bioavailability orally administered of HCT. This study aims to evaluate the sub-chronic toxicity of S-SNEDDS HCT formulations by examining biochemical parameters (SGOT, SGPT, BUN, and creatinine), and histopathological analysis of liver, kidney, and heart in male Wistar strain rats. An experimental design with five distinct treatment groups was utilized: negative control (CMC-Na 0,5%), S-SNEDDS base (aerosil), positive control (pure HCT 25 mg/kg BW), S-SNEDDS HCT (25 mg/kg BW), and satellite group (S-SNEDDS HCT 50 mg/kg BW). The treatment spanned for 28-days, followed by a 14-days observation period with no treatment for the satellite group.  The results showed that SGPT, BUN, and creatinine remained normal across all groups, suggesting the absence of liver or kidney damage. Histopathology analysis shows structural changes in the form of degeneration, necrosis, and infiltration of inflammatory cells mainly in the pure HCT and S-SNEDDS HCT groups, however in the satellite group the damage may return to normal when administration is stopped.